Advanced health insurance system using smart contract of ethereum blockchain - Tushar, Mehedi Hasan; Abdullah, Sifat; Shad, Aar Rafi Shahriar; Hyee, MD. Hisam Bin; Hesham, Sheblee Mohammad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.